Assessment of Preschool’s Inclusive Participation in Social Responsibility Program Under Institutional Pressure: Evidence From China - Lv, Yang; Ma, Chenwei; Wu, Min; Li, Xiaohan; Hao, Xinxin (Frontiers in Psychology, 2022)
China set the goal of expanding early childhood education (ECE) in 2018, by encouraging the development of public interest kindergartens (PIK) to provide high-quality, low-cost preschool services to the general public. This is in response to the challenges of accessibility, affordability, and accountability besetting China’s current ECE system. However, the transition towards PIK has been slow due to various complex problems, including the lackluster willingness of ECE providers to become PIK. To better understand the challenges leading to low participation, this study explores the external pressures affecting ECE providers and evaluates the external factors that influence their level of social responsibility. A stratified-random sampling questionnaire survey solicited responses from 832 ECE personnel representing 261 kindergartens from across China. Our findings suggest that institutional pressure has a positive effect on social responsibility and inclusive participation. We also found that institution visibility positively regulates the relationship between institutional pressure and social responsibility. At the same time, the level of environmental perception positively governs the relationship between social responsibility and participation willingness. Kindergartens should have certain social values, including assuming certain behaviors and participating in social activities in the spirit of social service.